DIMENSI KECAKAPAN HIDUP (LIFE SKILL) DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Hari Amirullah Rachman (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2009)
Life skills are essentially those abilities that help promote mental well-being and competence in young people as they face the realities of life. Most development professionals agree that life skills are generally applied in the context of health and social events. Children like to try out different ways, experiment with different materials, and see what they can do creatively to grasp the life skill. Finding different ways to exspressing themselves physically satisfies the urge for life skill action. But it must be their ways, their ides, and their accomplishment. Physical education gives children opportunity for exploratory and creative activity toward life skill. Children need an opportunity to tray out their own ideas, solve some of their own life problems and bring forth life skill development of their own origin. Keywords: Life skill, physical education